EREMURUS LACTIFLORUS O. FEDTSCH IN TASHKENT BOTANICAL GARDEN. (XANTHORRHOEACEAE) PLANT LEAF STRUCTURAL CHARACTERISTICS (Scientific journal of the Fergana State University, 2023)
In this article, the anatomical structure of the leaf of Eremurus lactiflorus, an endemic plant listed in the Red Book of Uzbekistan, specific diagnostic and adaptive structural features and conditions for introduction in the Tashkent botanical garden.